(untitled) (Conference Zone, 2022)
Based on primary sources such as periodicals and scientific literature, this article describes the state policy on the role of women in the public life of the Bukhara People’s Soviet Republic, created in 1920-1924 after the overthrow of the Emir of Bukhara